Fundação Casa. a mútua descoberta da realidade do outro - Rosa, Edvanda Bonavina da [UNESP] (My University, 2012)
In this paper we present a report of a project developed with young people who were in detention on the CASA Foundation, former FEBEM in Araraquara, in the period in which the activity occurred. Our goal with the project was twofold: that our presence at the Foundation supports the young people in that institution with leisure and social reintegration, and to enable students to make experience of new strategies for teaching undergraduate and citizenship training. The project developed there was entitled "The Art of Storytelling" and, and despite its catchy title, actually had a much less ambitious goal, which was not just enable artists to exercise the storytelling, but chiefly to raise awareness that our worldview and our inner lives are made up by micronarratives, which not only place us in the universe into which we belong and also creates our own identity. Having this perspective as a starting point and following the theoretical assumptions of Paulo Freire, for whom the learning process is interactive and based on the exchange of experiences, we held five meetings and the experience was enriching, both for students and for the Foundation´s youngs that took part in this activity.

Neste trabalho apresentamos o relato de um projeto desenvolvido com jovens em situação de detenção, que estavam na Fundação CASA26, antiga FEBEM, em Araraquara, no período em que a atividade ocorreu. Nosso objetivo com o projeto era duplo: contribuir com nossa presença na Fundação para a reinserção social e o lazer dos jovens daquela Instituição, bem como possibilitar que os alunos participantes fizessem a experiência de novas estratégias para o ensino de Graduação e de formação para a cidadania. O projeto que desenvolvemos lá intitulou-se “A arte de contar histórias” e, embora tenha um título atraente, na verdade tinha um objetivo bem menos ambicioso, que era não o de formar artistas aptos ao exercício da contação, mas suscitar a consciência de que nossa visão de mundo e nossa vida interior são constituídas por micronarrativas, que não só nos situam no universo ao qual pertencemos como também formam nossa própria identidade. Tendo essa perspectiva como ponto de partida e seguindo a linha teórica de Paulo Freire, para quem o processo de aprendizado é interativo e baseado na troca de experiências, realizamos cinco encontros e a experiência foi enriquecedora, tanto para os estudantes quanto para os jovens da Fundação que tomaram parte nessa atividade.
Keywords: Stories; Storytelling; Social rehabilitation; Histórias; Contação; Reinserção social